(untitled) (Global Journal of Medical Research, 2015)
56 year old male presented with one month history of vomiting with abdominal pain; hemogram suggested polycythemia with hemoglobin of 16.5-18.1gm%, gastroscopy showed pan gastritis, bone marrow smear, biopsy showed erythroid, megakaryocytic hyperplasia;ultra sonogram abdomen, pelvis did not show any significant abnormality; patient improved with parenteral hydration, proton pump inhibitors; after 7 months he returned with weakness, weight loss; hemoglobin alone had increased to 19 to 20gm%, with a hematocrit of 56.1%, other cell lines were not involved, suggesting secondary polycythemia; CT scan brain revealed Cerebellar Hemangioblastoma with obstructive hydrocephalus; emergency ventriculo peritoneal shunt was performed, followed by excision of the tumor; patient recovered and hemoglobin normalized.